Willingness to accept malaria vaccine among caregivers of under-5 children in Southwest Ethiopia: a community based cross-sectional study - Getachew Asmare (Malaria Journal, 2022)
Abstract Background Malaria is widespread in Ethiopia and has been a major cause of illness and death in that country. Therefore, Ethiopia has been exerting enormous efforts towards eliminating malaria by 2030. In the context of comprehensive malaria control, the malaria vaccine is used for the prevention of Plasmodium falciparum malaria in children living in regions with moderate- to-high malaria transmission. Methods A community-based cross-sectional study was conducted among caregivers of children under the age of five throughout the months of September 2021. A structured interviewer-administered questionnaire was designed for data collection, and binary logistic regression analysis was used. The final result of the association was determined based on an adjusted odds ratio (AOR) at a 95% confidence interval (CI) level, and p < 0.05 indicated statistical significance. Results A total of 406 caregivers of children under the age of 5 were interviewed. Overall, 131 (32.3%) respondents were willing to vaccinate their children. Marital status (AOR = 1.243; 95% CI 1.021–3.897), knowledge (AOR = 3.120; 95% CI 1.689–5.027), and previous experience with childhood vaccination (AOR = 2.673; 95% CI 1.759–4.101) were found to be significantly associated with willingness to accept a malaria vaccine for their children, at p < 0.05. Conclusions and recommendations The willingness to accept a malaria vaccine for children among caregivers of children under the age of five was low in the study area. Thus, health education and communication are crucial for alleviating poor knowledge about malaria vaccines.